Efficacy and Safety of High Potent P2Y12 Inhibitors Prasugrel and Ticagrelor in Patients With Coronary Heart Disease Treated With Dual Antiplatelet Therapy: A Sex‐Specific Systematic Review and Meta‐Analysis. Issue 4 (18th February 2020) - Schreuder, Michelle M.; Badal, Ricardo; Boersma, Eric; Kavousi, Maryam; Roos‐Hesselink, Jolien; Versmissen, Jorie; Visser, Loes E.; Roeters van Lennep, Jeanine E.
Abstract : Background: Sex differences in efficacy and safety of dual antiplatelet therapy remain uncertain because of the underrepresentation of women in cardiovascular trials. The aim of this study was to perform a sex‐specific analysis of the pooled efficacy and safety data of clinical trials comparing a high potent P2Y12 inhibitor+aspirin with clopidogrel+aspirin in patients with acute coronary syndrome. Methods and Results: A systematic literature search was performed. Randomized clinical trials that compared patients following percutaneous coronary intervention/acute coronary syndrome who were taking high potent P2Y12 inhibitors+aspirin versus clopidogrel+aspirin were selected. Random effects estimates were calculated and relative risks with 95% CIs on efficacy and safety end points were determined per sex. We included 6 randomized clinical trials comparing prasugrel/ticagrelor versus clopidogrel in 43 990 patients (13 030 women), with a median follow‐up time of 1.06 years. Women and men had similar relative risk (RR) reduction for major cardiovascular events (women: RR, 0.89 [95% CI, 0.80–1.00; men: RR, 0.84 [95% CI, 0.79–0.91) ( P for interaction=0.39). Regarding safety, women and men had similar risk of major bleeding by high‐potency dual antiplatelet therapy (RR, 1.18 [95% CI, 0.98–1.41] versus RR, 1.03 [95% CI, 0.93–1.14]) ( P for interaction=0.20). Conclusions: The small and statistically insignificant difference in efficacy and safety estimates of high‐potency dual antiplatelet therapy between women and men following percutaneous coronary intervention/acute coronary syndrome do not justify differential dual antiplatelet therapy treatment for both sexes.